Efficiency and soil contamination during underground application of insecticides: control of leaf-cutting ants with thermal foggers - Bollazzi, M.; Forti, L. C. [UNESP]; Moreira, S. [UNESP]; Roces, F. (Springer, 2014)
There are several types of potential hazards associated with the use of pesticides, among them, soil contamination during their underground application. The trade-off between control effectiveness and soil contamination can be observed during the control of leaf-cutting ants using thermal fogs in South American agricultural and forest plantations. This work was aimed at simultaneously assessing fog penetration into the soil around the application point, as a measure of contamination, and fog presence inside nest chambers of the grass-cutting ant Atta capiguara, as a measure of control effectiveness. For that, we have implanted fog sensors both into the soil around the application point and inside fungus chambers. Results showed that thermal fogging can be considered as an effective way for controlling leaf-cutting ants, since fog actually entered into the fungus chambers of A. capiguara after an average of 7 min. Nevertheless, after 3 min, i.e. long before reaching the fungus chambers, fog penetrated laterally 0.5 m into the soil, and at a depth of 1 m. At the time the fungus chambers were reached, the fog extended over 1.5 m across the soil. Thus, assuming a radial spread of fog, the total volume of contaminated soil around the application point averaged almost one cubic meter. Given the need of using thermal fogging for the control of Atta leaf-cutting ants due to both the economic damage they produce and the lack of other effective control methods under particular circumstances, associated environmental costs of thermal fogging as well as possible mitigation measures are discussed.
Keywords: Leaf-cutting ants; Atta capiguara; Control; Thermal fogging; Effectiveness; Soil contamination